Parvovirus B19 infection masquerading as relapsed acute lymphoblastic leukaemia following haematopoietic stem cell transplantation. Issue 8 (17th August 2020) - Larkin, Trisha; Li, Peng; Horn, Biljana
Abstract : A 7-year-old boy presented with a constellation of bone pain, a skeletal lesion, and pancytopenia after undergoing allogeneic haematopoietic stem cell transplantation for recurrent acute B-cell lymphoblastic leukaemia. Investigations to rule out leukaemia recurrence were unremarkable. Due to presence of maturation arrest in erythropoiesis with giant pronormoblasts and aberrant intranuclear inclusions on a bone marrow aspirate, parvovirus B19 (PVB-19) staining was completed and confirmed the diagnosis of disseminated PVB-19. Though PVB-19 infection after solid organ transplantation was reported in the literature as early as 1986, acquired PVB-19 viremia presenting with a solitary bone lesion is a novel presentation in paediatrics.